PENGARUH VARIASI WAKTU TAHAN CARBURIZING TERHADAP SIFAT MEKANIS BAJA AISI 1045 DENGAN MEDIA PENDINGIN AIR TDS NOL - Prasetyono, Bayu; Hartono, Priyagung; Marlina, Ena (UNIVERSITAS ISLAM MALANG, 2015)
Steel in the two-wheeled world automotive industry as the main raw material for the manufacture of gears. Hence the need for engineering mechanical properties of the steel to improve its quality. Steps in the mechanical properties of the steel engineering is the process of heat treatment, one of the heat treatment process to harden the steel surface is carburizing. The purpose of this study was to determine the effect of time variation carburizing resistant to mechanical properties of AISI 1045 steel with zero TDS water. Temperature carburizing wear 950 ? C. Carburizing process variations holding time is 1; 3; and 5 hours. Material hardness and toughness testing using vickers and charpy test. The results showed that the increasing violence after the carburizing process toughness tends to decrease. Before the process of carburizing average value 209.166 HVN hardness and toughness 0.8425 Joules / mm2. Holding time 1 hour carburizing process average value 417.13 HVN hardness and toughness 0.3975 Joules / mm2. Holding time 3 hours carburizing process average value 347.866 HVN and toughness 0.3333 Joules / mm2. Holding time 5 hours carburizing process average value 430.4 HVN hardness and toughness 0.3698 Joules / mm2